Thromboembolic events, recurrent bleeding and mortality after resuming anticoagulant following gastrointestinal bleeding - Chai-Adisaksopha, Chatree; Hillis, Christopher; Monreal, Manuel; Witt, Daniel M.; Crowther, Mark (Thrombosis and Haemostasis, 2015)
Gastrointestinal (GI) bleeding commonly complicates anticoagulant therapy. We aimed to systematically review the published literature to determine the risk of thromboembolism, recurrent GI bleeding and mortality for patients on long-term anticoagulation who experience GI bleeding based on whether anticoagulation therapy was resumed. We performed a systematic review of phase III randomised controlled trials and cohort studies in patients with atrial fibrillation or venous thromboembolism who received oral anticoagulant. We searched MEDLINE, EMBASE and CENTRAL (from 1996-July 2014), conferences abstracts (from January 2006-July 2014) and www.clinicaltrials.gov (up to the last week of July 2014) with no language restriction. Two reviewers independently performed study selection, data extraction and study quality assessment. A total of three studies were included in the meta-analysis. The resumption of warfarin was associated with a significant reduction in thromboembolic events (hazard ratio [HR] 0.68, 95 % confidence interval [CI] 0.52 to 0.88, p < 0.004, I2=82 %). There was an increase in recurrent GI bleeding but not statistically significant for patients who restarted warfarin compared to those who did not (HR 1.20, 95 % CI 0.97 to 1.48, p = 0.10, I2 = 0 %). Resumption of warfarin was associated with significant reduction in mortality (HR 0.76, 95 % CI 0.66 to 0.88, p < 0.001, I2 = 87 %). This meta-analysis demonstrates that resumption of warfarin following interruption due to GI bleeding is associated with a reduction in thromboembolic events and mortality without a statistically significant increase in recurrent GI bleeding.Institution where the work was performed: McMaster University, Hamilton, Ontario, Canada.
Keywords: Anticoagulants; bleeding; warfarin; gastrointestinal haemorrhage; thromboembolism